Primary Closure versus Bedside Silo and Delayed Closure for Gastroschisis: A Truncated Prospective Randomized Trial - Poola, Ashwini S.; Aguayo, Pablo; Fraser, Jason D.; Hendrickson, Richard J.; Weaver, Katrina L.; Gonzalez, Katherine W.; St Peter, Shawn D. (European Journal of Pediatric Surgery, 2019)
Background We report a prospective randomized trial comparing primary closure (PC) to bedside silo and delayed closure (DC) for babies with gastroschisis.Materials and Methods Patients were randomized to PC versus DC. We excluded those with atresia/necrosis, <34 weeks' gestation, or congenital anomalies. The primary outcome was length of stay (LOS).Results A total of 38 patients were included from August 2011 to August 2016; 18 patients underwent DC and 20 PC. There were no differences in gestational age or birth weight. Fifty percent of PC patients were successfully closed with the rest closed at a median of 4 days (interquartile range [IQR]: 2–4 days). DC patients were closed at a median of 4 days after silo placement (IQR: 2–5.8 days). None of the patients in this series developed abdominal compartment syndrome after closure. Median LOS, median time to enteral tolerance, and median time on ventilation were not statistically different. Two patients (one DC and one PC) had bowel ischemia and necrosis following silo placement requiring reoperation. Four patients (two DC and two PC) were noted to have small umbilical defects; none have yet required operative correction.Conclusion There were no differences seen between PC and DC in LOS, time to enteral feeds, or ventilator times.
Keywords: gastroschisis; randomized; silo; primary closure